2019
DOI: 10.1016/j.anr.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress among Adolescents in Laos, Mongolia, Nepal, and Sri Lanka

Abstract: The purpose of this study was to explore psychological distress and examine the relationship between this distress and individual, family, and school factors among adolescents in four low-and middle-income countries (LAMICs) in Asia (i.e., Laos, Mongolia, Nepal, and Sri Lanka). Methods: A total of 4,098 adolescents attending public schools in the four LAMICs were surveyed as part of the Healthy School Development Project, which aimed to develop school capacity for improving (1) health among all school members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
8
23
1
Order By: Relevance
“…Several social-environmental factors (parental disrespect of privacy and in unadjusted analysis passive smoking, low peer support, low parental support, experience of hunger and school truancy) were found to be associated with WISD. These results are consistent with various previous investigations [ 13 , 14 , 15 , 16 ] and call for programmes improving parental and peer support.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several social-environmental factors (parental disrespect of privacy and in unadjusted analysis passive smoking, low peer support, low parental support, experience of hunger and school truancy) were found to be associated with WISD. These results are consistent with various previous investigations [ 13 , 14 , 15 , 16 ] and call for programmes improving parental and peer support.…”
Section: Discussionsupporting
confidence: 93%
“…Psychosocial distresses associated with WISD or psychological distress may include loneliness [ 12 ], having no close friends [ 13 ], interpersonal violence [ 13 ], and bullying victimization [ 12 ]. Socio-environmental factors associated with WISD or psychological distress, may include experience of hunger [ 14 ], low peer and low parental support [ 13 , 14 , 15 , 16 ] and school truancy [ 15 ]. Health risk behaviours associated with WISD or psychological distress, may include substance use [ 14 , 17 , 18 ], sedentary behaviour [ 8 , 19 ], frequent fast food consumption [ 20 ], frequent soft drink intake [ 20 ], fast food intake and sedentary behaviour [ 21 ], sexual behaviour [ 14 ] and injury [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with former research findings [9,10,19,34], this survey showed that having social distress, such as having no close friends, bullying victimization, infrequently physically attacked and frequently involved in physical fighting increased the odds for psychological distress. Students exposed to interpersonal violence victimization may worry about further or future victimization increasing psychological distress.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of moderate to severe PD (measured with the Kessler K-10) was 10.5% among school-going adolescents in India [6], and among adolescents in four Asian countries, PD was 32.9% (presence of any item: suicidal ideation, plans and suicide attempts, loneliness, sadness and anxiety) [7]. In a study among adolescents in Afghanistan, the prevalence of PD was 27.7% (≥2 items of no close friends, loneliness, anxiety, suicidal ideation, and suicide attempt) [8], and among adolescents in Iran, 17.7% (≥3 items of worthless, anxious, angriness, confusion, and insomnia) had PD [9].…”
Section: Introductionmentioning
confidence: 99%